Presentación - Montanaro Mena, María Esther (2021)
The purpose of this issue has been to gather a set of reflections prepared by specialists, both national and international about the past and present history of a number of different indigenous latin american peoples. The eleven texts collected here were elaborated from a rich variety of approaches, periodicities, documentary sources, and analytical perspectives which account for the persistence of structural and common problems such as racism and the dispossession of territories, patrimonies and knowledges; also, of limited and even failed public policies which explain to a large degree why structural violence is so rooted in the national states of our region. Similarly, this issue marks the record of the agency power of indigenous peoples, of the richness contained in indigenous orality, in their tongues, their poetry, their means of communication and their communitary experiences which resist against the predatory capital’s logic. Thus, the Universidad Nacional History Journal (UNA) pretends to contribute to a debate as necessary as it is urgent, in order to face the Bicentennial of the Indepence of Central America’s commemoration.